Word Recognition System Using ANN (International Journal of Engineering and Computer Science, 2016)
: This paper deals with the concept of Optical Character Recognition (OCR) and its various   stages like  pre-processing,   segmentation,   feature   extraction,   classification   and   post-processing.   The   main objective of this paper is:• To study the existing techniques for recognition of handwritten Hindi text.• To develop and apply the new segmentation technique on the handwritten Hindi text collected from different users.  .• To design a new feature set for the handwritten Hindi text.• Recognition of handwritten Hindi text.